Proceedings of the Thirteenth International Society of Sports Nutrition (ISSN) Conference and Expo. Issue 1 (September 2016) - Ramaswamy, Lalitha; Velraja, Supriya; Escalante, Guillermo; Harvey, Phil; Alencar, Michelle; Haddock, Bryan; Harvey, Phil; Escalante, Guillermo; Alencar, Michelle; Haddock, Bryan; Durkalec-Michalski, Krzysztof; Jeszka, Jan; et al.
Table of contents P1 Impact of antioxidant-enriched nutrient bar supplementation on the serum antioxidant markers and physical fitness components of track and field athletes Lalitha Ramaswamy, Supriya Velraja P2 The effects of phosphatidic acid supplementation on fitness levels in resistance trained women Guillermo Escalante, Phil Harvey, Michelle Alencar, Bryan Haddock P3 The effects of phosphatidic acid supplementation on cardiovascular risk factors in resistance trained men Phil Harvey, Guillermo Escalante, Michelle Alencar, Bryan Haddock P4 The efficacy of sodium bicarbonate supplementation on physical capacity and selected biochemical markers in elite wrestlers Krzysztof Durkalec-Michalski, Jan Jeszka, Bogna Zawieja, Tomasz Podgórski P5 Effects of different nutritional strategies in hydration and physical performance in healthy well-trained males Ana Paula Trussardi Fayh, Alexandre Hideki Okano, Amanda Maria de Jesus Ferreira P6 Reduction of plasma creatine concentrations as an indicator of improved bioavailability Ralf Jäger, Martin Purpura, Roger C Harris P7 Effect of three different breakfast meals on energy intake and nutritional status in college-age women Molly M. Krause, Kiley A. Lavanger, Nina O. Allen, Allison E. Lieb, Katie A. Mullen, Joan M. Eckerson P8 Accuracy of the ASA24® Dietary Recall system for assessing actual dietary intake in normal weight college-age women. Kiley A. Lavanger, Molly M. Krause, Nina O. Allen, Allison E. Lieb, Katie A. Mullen, Joan M. Eckerson P9 β-aminoisobutyric acid does not regulate exercise induced UCP-3 expression in skeletal muscle Elisa Morales, Jeffrey Forsse, Thomas Andre, Sarah McKinley, Paul Hwang, Grant Tinsley, Mike Spillane, Peter Grandjean, Darryn Willoughby P10 The ability of collegiate football athletes to adhere to sport-specific nutritional recommendations A. Jagim, G. Wright, J. Kisiolek, M. Meinking, J. Ochsenwald, M. Andre, M.T. Jones, J. M. Oliver P11 A single session of low-volume high intensity interval exercise improves appetite regulation in overweight men Victor Araújo Ferreira, Daniel Costa de Souza, Victor Oliveira Albuquerque dos Santos, Rodrigo Alberto Vieira Browne, Eduardo Caldas Costa, Ana Paula Trussardi Fayh P12 Acute effects of oral peppermint oil ingestion on exercise performance in moderately-active college students Suresh T. Mathews, Haley D. Bishop, Clara R. Bowen, Yishan Liang, Emily A. West, Rebecca R. Rogers, Mallory R. Marshall, John K. Petrella P13 Associations in body fat and liver triglyceride content with serum health markers in sedentary and exercised rats fed a ketogenic diet, Western diet or standard chow over a 6-week period A. Maleah Holland, Wesley C. Kephart, Petey W. Mumford, C. Brooks Mobley, Ryan P. Lowery, Jacob M. Wilson, Michael D. Roberts P14 Physiological changes following competition in male and female physique athletes: A pilot study Eric T. Trexler, Katie R. Hirsch, Bill I. Campbell, Meredith G. Mock, Abbie E. Smith-Ryan P15 Relationship between cognition and hydration status in college students at a large Southwestern university Kate Zemek, Carol Johnston P16 Whey protein-derived exosomes increase protein synthesis in C2C12 myotubes C. Brooks Mobley, Petey W. Mumford, David D. Pascoe, Christopher M. Lockwood, Michael E. Miller, Michael D. Roberts P17 The effect of three different energy drinks on 1.5-mile running performance, oxygen consumption, and perceived exertion Gabriel J. Sanders, Willard Peveler, Brooke Warning, Corey A. Peacock P18 The Ketogenic diet improves rotarod performance in young and older rats Wesley C. Kephart, Petey W. Mumford, Ryan P. Lowery, Michael D. Roberts, Jacob M. Wilson P19 Absorption of bonded arginine silicate compared to individual arginine and silicon components David Sandler, Sara Perez Ojalvo, James Komorowski P20 Effects of a high (2.4 g/kg) vs. low/moderate (1.2 g/kg) protein intake on body composition in aspiring female physique athletes engaging in an 8-week resistance training program Bill I. Campbell, Danielle Aguilar, Andres Vargas, Laurin Conlin, Amey Sanders, Paola Fink-Irizarry, Layne Norton, Ross Perry, Ryley McCallum, Matthew R. Wynn, Jack Lenton P21 Effects of a high (2.4 g/kg) vs. low/moderate (1.2 g/kg) protein intake on maximal strength in aspiring female physique athletes engaging in an 8-week resistance training program Bill I. Campbell, Chris Gai, Seth Donelson, Shiva Best, Daniel Bove, Kaylee Couvillion, Jeff Dolan, Dante Xing, Kyshia Chernesky, Michael Pawela, Andres D. Toledo, Rachel Jimenez P22 Monitoring of female collegiate athletes over a competitive season reveals changes in nutritional biomarkers M. Rabideau, A. Walker, J. Pellegrino, M. Hofacker, B. McFadden, S. Conway, C. Ordway, D. Sanders, R. Monaco, M. S. Fragala, S. M. Arent P23 Comparison of prediction equations to indirect calorimetry in men and women athletes Jason D. Stone, Andreas Kreutzer, Jonathan M. Oliver, Jacob Kisiolek, Andrew R. Jagim P24 Regional variations in sweat-based electrolyte loss and changes in plasma electrolyte content in Division I female athletes over the course of a competitive season M. Hofacker, A. Walker, J. Pellegrino, M. Rabideau, B. McFadden, S. Conway, D. Sanders, C. Ordway, R. Monaco, M. S. Fragala, S. M. Arent P25 In-season changes in plasma amino acid levels in Division I NCAA female athletes Ozlem Tok, Joseph K. Pellegrino, Alan J. Walker, David J. Sanders, Bridget A. McFadden, Meaghan M. Rabideau, Sean P. Conway, Chris E. Ordway, Marissa Bello, Morgan L. Hofacker, Nick S. Mackowski, Anthony J. Poyssick, Eddie Capone, Robert M. Monaco, Maren S. Fragala, Shawn M. Arent P26 Effects of a ketogenic diet with exercise on serum markers of bone metabolism, IGF-1 and femoral bone mass in rats Petey W. Mumford, A. Maleah Holland, Wesley C. Kephart, Ryan P. Lowery, C. Brooks Mobley, Romil K. Patel, Annie Newton, Darren T. Beck, Michael D. Roberts, Jacob M. Wilson, Kaelin C. Young P27 Casein supplementation in trained men and women: morning versus evening Tobin Silver, Anya Ellerbroek, Richard Buehn, Leo Vargas, Armando Tamayo, Corey Peacock, Jose Antonio P28 A high protein diet has no harmful effects: a one-year crossover study in resistance-trained males Anya Ellerbroek, Tobin Silver, Richard Buehn, Leo Vargas, Armando Tamayo, Corey Peacock, Jose Antonio P29 SUP (Stand-up Paddling) athletes: nutritional intake and body composition Adam Pollock, Anya Ellerbroek, Tobin Silver, Corey Peacock, Jose Antonio P30 The effects of 8 weeks of colostrum and bio-active peptide supplementation on body composition in recreational male weight lifters A. Kreutzer, P. Zavala, S. Fleming, M. Jones, J. M. Oliver, A. Jagim P31 Effects of a Popular Women's Thermogenic Supplement During an Energy-Restricted High Protein Diet on Changes in Body Composition and Clinical Safety Markers Cody T. Haun, Petey W. Mumford, Parker N. Hyde, Ciaran M. Fairman, Wesley C. Kephart, Darren T. Beck, Jordan R. Moon, Michael D. Roberts, Kristina L. Kendall, Kaelin C. Young P32 Three days of caffeine consumption following caffeine withdrawal yields small strength increase in knee flexors Geoffrey M Hudson, Tara Hannings, Kyle Sprow, Loretta DiPietro P33 Comparison of cellular nitric oxide production from various sports nutrition ingredients Doug Kalman, Sara Perez Ojalvo, James Komorowski P34 The effects of 8 weeks of bio-active peptide supplementation on training adaptations in recreational male weight lifters P. Zavala, S. Fleming, M. Jones, J. Oliver, A. Jagim P35 Effects of MusclePharm Assault BlackTM on lower extremity spinal excitability and postactivation potentiation: A pilot study Brian Wallace, Haley Bergstrom, Kelly Wallace P36 Effects of four weeks of Ketogenic Diet alone and combined with High intensity Interval Training or Continuous-Moderate intensity on body composition, lipid profile and physical performance on healthy males Matias Monsalves-Alvarez, Sebastian Oyharçabal, Victoria Espinoza P37 Effect of branched-chain amino acid supplementation on creatine kinase, muscular performance, and perceived muscle soreness following acute eccentric exercise Trisha A. VanDusseldorp, Kurt A. Escobar, Kelly E. Johnson, Nathan Cole, Terence Moriarty, Matthew Stratton, Marvin R. Endito, Christine M. Mermier, Chad M. Kerksick P38 Effects of endurance training on markers of ribosome biogenesis in rodents fed a high fat diet Matthew A. Romero, C. Brooks Mobley, Melissa Linden, Grace Margaret-Eleanor Meers, R. Scott Rector, Michael D. Roberts P39 The effects of acute citrulline-malate on lower-body isokinetic performance in recreationally active individuals Joshua L Gills, Hocheng Lu, Kimberly Parker, Chris Dobbins, Joshua N Guillory, Braden Romer, David Szymanski, Jordan Glenn P40 The effect pre-ingested L-isoleucine and L-leucine on blood glucose responses and glycemic hormones in healthy inactive adults: Preliminary data. Daniel E. Newmire, Eric Rivas, Sarah E. Deemer, Robert Wildman, Victor Ben-Ezra P41 Does protein and source impact substrate oxidation and energy expenditure during and after moderate intensity treadmill exercise? C Kerksick, B Gieske, R Stecker, C Smith, K Witherbee P42 Effects of a pre-workout supplement on peak power and power maintenance during lower and upper body testing Michael T. Lane, M. Travis Byrd, Zachary Bell, Emily Frith, Lauren M.C. Lane P43 Effects of a pre-workout supplement on peak power production during lower and upper body testing in college-age females Michael T. Lane, M. Travis Byrd, Zachary Bell, Emily Frith, Lauren M.C. Lane P44 A comparison of whey versus casein protein supplementation on resting metabolic rate and body composition: a pilot study Corey A. Peacock, Tobin A. Silver, Megan Colas, Mauricio Mena, Winter Rodriguez, Gabriel J. Sanders, Jose Antonio P45 A novel mixed-tocotrienol intervention enhances recovery after eccentric exercise: preliminary findings Andrea Vansickle, Brittany DiFiore, Stephanie Stepp, Grant Slack, Bridget Smith, Kayla Ruffner, Ronald Mendel, Lonnie Lowery P46 The effects of post-exercise ingestion of a high molecular weight glucose on cycle performance in female cyclists Katie R. Hirsch, Meredith G. Mock, Malia M.N. Blue, Eric T. Trexler, Erica J. Roelofs, Abbie E. Smith-Ryan P47 Inclusive vs. exclusive dieting and the effects on body composition in resistance trained individuals Laurin Conlin, Danielle Aguilar, Bill I. Campbell, Layne Norton, Katie Coles, Eric T. Trexler, Nic Martinez P48 A whey protein hydrolysate may positively augment resting metabolism compared to intact whey protein Jordan M. Joy, Roxanne M. Vogel, Thomas H. Hoover, K. Shane Broughton P49 Seven days of high and low dose creatine nitrate supplementation I: hepatorenal, glucose and muscle enzyme function R Dalton, R Sowinski, T Grubic, PB Collins, A Colletta, A Reyes, B Sanchez, M Kozehchain, YP Jung, C Rasmussen, P Murano, CP Earnest, M Greenwood, RB Kreider P50 Seven days of high and low dose creatine nitrate supplementation II: performance T Grubic, R Dalton, R Sowinski, PB Collins, A Colletta, A Reyes, B Sanchez, M Kozehchain, YP Jung, C Rasmussen, P Murano, CP Earnest, M Greenwood, RB Kreider P51 Seven days of high and low dose creatine nitrate supplementation III: hemodynamics R Sowinski, R Dalton, T Grubic, PB Collins, A Colletta, A Reyes, B Sanchez, M Kozehchain, YP Jung, C Rasmussen, P Murano, CP Earnest, M Greenwood, RB Kreider P52 The efficacy of a β-hydroxy-β-methylbutyrate supplementation on physical capacity, body composition and biochemical markers in highly-trained combat sports athletes Krzysztof Durkalec-Michalski, Jan Jeszka, Tomasz Podgórski P53 Does protein and source impact substrate oxidation and energy expenditure during and after moderate intensity treadmill exercise? C Kerksick, B Gieske, R Stecker, C Smith, K Witherbee P54 Effects of 30 days of Cleanse™ supplementation on measure of body composition, waist circumference, and markers of gastrointestinal distress in females Stacie Urbina, Emily Santos, Katelyn Villa, Alyssa Olivencia, Haley Bennett, Marissa Lara, Cliffa Foster, Colin Wilborn, Lem Taylor P55 The effects of moderate- versus high-load training on body composition, muscle growth, and performance in college aged females Jason M Cholewa, Amy Hewins, Samantha Gallo, Ashley Micensky, Christian De Angelis, Christopher Carney, Bill Campbell, Laurin Conlin, Layne Norton, Fabricio Rossi P56 Effect of a multi-ingredient preworkout supplement on cognitive function and perceptions of readiness to perform MS Koozehchian, PB Collins, R Sowinski, T Grubic, R Dalton, A O'Connor, SY Shin, Y Peter Jung, BK Sanchez, A Coletta, M Cho, A Reyes, C Rasmussen, CP Earnest, PS Murano, M Greenwood, RB Kreider